Valuation of holding companies listed on Borsa Istanbul - Güven, Sena Nur (Graduate School, 2023)
Businesses have been growing and expanding their scope and territories of operations in response to the development of the products and services markets as a result of globalization. Therefore, organisations must adapt to the changes in order to maintain continuity and gain a competitive edge. Numerous regional, national, and international economic agreements as well as capital groupings were established as a result of these modifications. Holding corporations are one type of commercial arrangement between businesses. These organizations and their subsidiaries are very important for not only the global economy and stock markets, but also the Turkish economy and the Borsa Istanbul (BIST), where firms are listed in Turkiye. Consequently, given the significance of holding companies, computing fair values of these organizations is essential for investors, business owners, management team and other stakeholders. According to several studies, holding companies that are listed on stock exchange platforms throughout the world are traded with discount, which has different rates in different markets. For instance, the holdings in the United States of America (USA) are discounted between 10-15% whereas, the ratios in South Korea are between 30-60%. However, there is relatively few studies in the literature on the value of holding corporations in Turkiye. My goal for this thesis is to add to the literature by methodically valuing holding businesses in Turkey. In addition, I would like to provide scholars and investors an approach that is both statistically and practically useful. In this thesis, I studied on the holding firms, which met particular requirements, and their subsidiaries to understand whether holding companies listed on BIST are valued with discount, and if so, in which discount rate. The Sum of The Parts (SOTP) approach is used in this study to determine the valuations of holding corporations that meet several criteria and are listed on BIST. To uncover the answers to my research questions, then I compared the results with actual stock prices at the end of 2020. In the basis of SOTP method, a holding's value is calculated by its subsidiaries. The first approach applied according to this methodology is to multiply the determined fair value of each subsidiary by the holding company's ownership ratio and sum the values. The fair value of one share is then calculated by dividing the figure by the total number of outstanding shares. The overall value of non-public subsidiaries is considered to be proportionately equal to the computed value of public subsidiaries. Therefore, a crucial financial indicator is used to compute the ratio of public and non-public subsidiaries. Since the fair value of each share of the holding estimated by its publicly listed subsidiaries is known, the overall value of the holding is determined by multiplying the value of its publicly traded affiliates by the holding company as a whole. As a first step, the valuation method of the subsidiaries is determined. Mainly, holding companies have two types of subsidiaries: manufacturing firms and financial service firms. In the literature and practice, there are many different valuation methods, which enable to calculate fair value of any stock, and each of them have several advantages and disadvantages. One of the main methods is Discounted Cash Flow (DCF) and it has three breakdowns: Free Cash Flow to Firm (FCFF), Free Cash Flow to Equity (FCFE), Dividend Discount Model. Moreover, relative valuation and Excess Return Model (ERM) are other valuation methods. As per recommendations in the literature and considering the beneficial of the method, FCFF is applied to assess the fair value of manufacturing firms and ERM is applied to assess the fair value of financial service firms. The two main reasons why two different methods are applied for valuation are based on the different financial structure and the applied regulations. The second step of the thesis is determining the holding companies which fit several criteria. Considering the logic of SOTP, holding companies should have at least one publicly traded subsidiary, and the weight of the subsidiary or subsidiaries in the holding should reflect the holding's selected financial indicator, which is stakeholders' equity value, proportionally. Moreover, holding companies should be listed on BIST for at least three years, ideally at least five years. Although seventeen holding companies listed on Holdings & Investment Index (XHOLD), only five holding companies meet the criteria and so, these are valued. Totally, the five holding companies, which are Koç Holding (KCHOL), Sabancı Holding (SAHOL), and AG Anadolu Grubu Holding (AGHOL), Mazhar Zorlu Holding (MZHLD), and Eczacıbaşı Yatırım Holding (ECZYT), consist of 67% of XHOLD. In the third step, the subsidiaries of these five holding companies are calculated with either FCFF or ERM. Then, the holdings fair values are calculated by SOTP. As a result, it is found that the discount rate for KCHOL is %70, the rate for SAHOL is 86% and the rate for AGHOL is 81%. These three holdings consist of 64.18% of XHOLD at the end of 2020. Moreover, ECZYT is discounted by 15% and MZHLD is discounted by 37%. Consequently, this thesis demonstrates that holding firms in Turkiye are discounted between 15% and 86% when the holding values are derived from the valuation of their subsidiaries. These results belong to 2020 and to understand the existence of discount for different years, second approach is applied. According to the second approach, SOTP is used to calculate the holdings' values but instead of computing fair values of the subsidiaries, the market values are considered. Therefore, fair values of seventeen holding companies are calculated between 2011 and 2020 in this approach by using market value of their subsidiaries. As a result, in most cases, holdings are traded with discount either certain years or fully except one holding. As a result of the second approach, KCHOL is traded with discount by 62%, the rate for SAHOL is 71% and for AGHOL is 76%. Also, ECZYT is discounted as 14% and the rate for MZHLD is the same as the previous one, 55%. When the fair values of the holding companies are computed by using the market values of their subsidiaries, 67% of the index is traded with discount between 14% and 76%. The findings from both approaches are compared with the market values in 2020 since three values are available. In both cases, holding companies in Turkiye are traded with discount on the stock exchange market. However, the range of the rate is wider when market values are taken. These results indicate that holding companies listed on BIST has similar discount rate to Korean holding companies rather than the USA.
Borsa İstanbul'da yer alan holdinglerin değerlemesi
Businesses have been growing and expanding their scope and territories of operations in response to the development of the products and services markets as a result of globalization. Therefore, organisations must adapt to the changes in order to maintain continuity and gain a competitive edge. Numerous regional, national, and international economic agreements as well as capital groupings were established as a result of these modifications. Holding corporations are one type of commercial arrangement between businesses. These organizations and their subsidiaries are very important for not only the global economy and stock markets, but also the Turkish economy and the Borsa Istanbul (BIST), where firms are listed in Turkiye. Consequently, given the significance of holding companies, computing fair values of these organizations is essential for investors, business owners, management team and other stakeholders. According to several studies, holding companies that are listed on stock exchange platforms throughout the world are traded with discount, which has different rates in different markets. For instance, the holdings in the United States of America (USA) are discounted between 10-15% whereas, the ratios in South Korea are between 30-60%. However, there is relatively few studies in the literature on the value of holding corporations in Turkiye. My goal for this thesis is to add to the literature by methodically valuing holding businesses in Turkey. In addition, I would like to provide scholars and investors an approach that is both statistically and practically useful. In this thesis, I studied on the holding firms, which met particular requirements, and their subsidiaries to understand whether holding companies listed on BIST are valued with discount, and if so, in which discount rate. The Sum of The Parts (SOTP) approach is used in this study to determine the valuations of holding corporations that meet several criteria and are listed on BIST. To uncover the answers to my research questions, then I compared the results with actual stock prices at the end of 2020. In the basis of SOTP method, a holding's value is calculated by its subsidiaries. The first approach applied according to this methodology is to multiply the determined fair value of each subsidiary by the holding company's ownership ratio and sum the values. The fair value of one share is then calculated by dividing the figure by the total number of outstanding shares. The overall value of non-public subsidiaries is considered to be proportionately equal to the computed value of public subsidiaries. Therefore, a crucial financial indicator is used to compute the ratio of public and non-public subsidiaries. Since the fair value of each share of the holding estimated by its publicly listed subsidiaries is known, the overall value of the holding is determined by multiplying the value of its publicly traded affiliates by the holding company as a whole. As a first step, the valuation method of the subsidiaries is determined. Mainly, holding companies have two types of subsidiaries: manufacturing firms and financial service firms. In the literature and practice, there are many different valuation methods, which enable to calculate fair value of any stock, and each of them have several advantages and disadvantages. One of the main methods is Discounted Cash Flow (DCF) and it has three breakdowns: Free Cash Flow to Firm (FCFF), Free Cash Flow to Equity (FCFE), Dividend Discount Model. Moreover, relative valuation and Excess Return Model (ERM) are other valuation methods. As per recommendations in the literature and considering the beneficial of the method, FCFF is applied to assess the fair value of manufacturing firms and ERM is applied to assess the fair value of financial service firms. The two main reasons why two different methods are applied for valuation are based on the different financial structure and the applied regulations. The second step of the thesis is determining the holding companies which fit several criteria. Considering the logic of SOTP, holding companies should have at least one publicly traded subsidiary, and the weight of the subsidiary or subsidiaries in the holding should reflect the holding's selected financial indicator, which is stakeholders' equity value, proportionally. Moreover, holding companies should be listed on BIST for at least three years, ideally at least five years. Although seventeen holding companies listed on Holdings & Investment Index (XHOLD), only five holding companies meet the criteria and so, these are valued. Totally, the five holding companies, which are Koç Holding (KCHOL), Sabancı Holding (SAHOL), and AG Anadolu Grubu Holding (AGHOL), Mazhar Zorlu Holding (MZHLD), and Eczacıbaşı Yatırım Holding (ECZYT), consist of 67% of XHOLD. In the third step, the subsidiaries of these five holding companies are calculated with either FCFF or ERM. Then, the holdings fair values are calculated by SOTP. As a result, it is found that the discount rate for KCHOL is %70, the rate for SAHOL is 86% and the rate for AGHOL is 81%. These three holdings consist of 64.18% of XHOLD at the end of 2020. Moreover, ECZYT is discounted by 15% and MZHLD is discounted by 37%. Consequently, this thesis demonstrates that holding firms in Turkiye are discounted between 15% and 86% when the holding values are derived from the valuation of their subsidiaries. These results belong to 2020 and to understand the existence of discount for different years, second approach is applied. According to the second approach, SOTP is used to calculate the holdings' values but instead of computing fair values of the subsidiaries, the market values are considered. Therefore, fair values of seventeen holding companies are calculated between 2011 and 2020 in this approach by using market value of their subsidiaries. As a result, in most cases, holdings are traded with discount either certain years or fully except one holding. As a result of the second approach, KCHOL is traded with discount by 62%, the rate for SAHOL is 71% and for AGHOL is 76%. Also, ECZYT is discounted as 14% and the rate for MZHLD is the same as the previous one, 55%. When the fair values of the holding companies are computed by using the market values of their subsidiaries, 67% of the index is traded with discount between 14% and 76%. The findings from both approaches are compared with the market values in 2020 since three values are available. In both cases, holding companies in Turkiye are traded with discount on the stock exchange market. However, the range of the rate is wider when market values are taken. These results indicate that holding companies listed on BIST has similar discount rate to Korean holding companies rather than the USA.
Keywords: Borsa Istanbul; Borsa İstanbul; Investments; Yatırımlar